2007
DOI: 10.1017/s1355770x06003494
|View full text |Cite
|
Sign up to set email alerts
|

Does natural resource extraction mitigate poverty and inequality? Evidence from rural Mexico and a Lacandona Rainforest Community

Abstract: SummaryThe potential importance of natural resources for the livelihood of poor rural households has long been recognized but seldom quantified and analyzed. In this paper we examine distributional and poverty effects of natural resource extraction at the national, regional and community levels. To do this, we use new data from a national rural household survey and a community survey implemented in the Lacandona Rainforest (Selva Lacandona) of Mexico. First, we explore whether income from natural resource extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 16 publications
(21 reference statements)
1
52
0
8
Order By: Relevance
“…As developed in López-Feldman et al (2007), each source's contribution to the Gini coefficient could be observed as the product of its share on total output, its own source's Gini coefficient, and its correlation with the total output and can be expressed as…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As developed in López-Feldman et al (2007), each source's contribution to the Gini coefficient could be observed as the product of its share on total output, its own source's Gini coefficient, and its correlation with the total output and can be expressed as…”
Section: Discussionmentioning
confidence: 99%
“…To characterize the inequality level generated by agricultural output, we use the Gini coefficient decomposition proposed by Pyatt et al (1980) and Shorrocks (1982), and extended by López-Feldman et al (2007), which includes the marginal effects of different sources on overall yield inequality, focusing on the impact of water-related variables. The Gini coefficient is probably the most common inequality measure because of its simplicity and its desirable properties.…”
Section: Measuring Rural Income Distributionmentioning
confidence: 99%
“…In the case of the southern region of the country, a study by López-Feldman et al [55] shows that the population with a greater or extreme level of poverty receives greater improvement to its well-being once it exploits one of the common-use natural resources available in the zone, to include income from natural resources, economic inequality is decreased, the Gini coeffi cient was 0553 to 0583, with a difference of 0.028, similar to the results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The Gini coefficient is probably the most common inequality measure, because its simplicity and its desirable properties. This concentration ratio is widely used in many fields of economics as well as in ecology and agronomics, but there are fewer applications in agricultural and environmental economics together ( [39][40][41]). In a general context, it ranges from zero (equal distribution) to one (perfect inequality), and fulfills the properties of mean independence, population size independence, symmetry, and Pigou Dalton transfer sensitivity ( [42]).…”
Section: Distributional Efficiency Using the Decomposition Of The Ginmentioning
confidence: 99%